NOTES ON THE FISH RESOURCES OF THE BAHUDA ESTUARY, ORISSA, INDIA - Dash, S.; Mishra, S. S. (Journal of Indian Fisheries Association, 2007)
Estuaries form an important site for the zoologist as these are the places known to be very rich in food and nutrients and so, become nesting-cumbreeding grounds for many species and also, own good species diversity. Bahuda estuary of Orissa is located at the inter-state border of Orissa and Andhra Pradesh. Explored for many invertebrates, this estuary was not properly investigated for its rich fish fauna. Various surveys at Bahuda estuary revealed that it is an important site of study for the faunal diversity of fishes in the east coast. Forty-eight species belonging to 33 genera under eight orders and 22 families were examined referring standard literature· and methods. Most of the groups of fishes encountered are of commercial importance. Keywords: Fish resources, Bahuda estuary